VOCATIONAL ENGLISH TEACHERS’ ADAPTATION TO DEEP LEARNING PEDAGOGY DURING CURRICULUM REFORM - Nicke Yunita Moecharam; Gin Gin Gustine; Annisa Rahmadani; Nida Mujahidah Fathimah; Susan Santika (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2026)
Curriculum reform in vocational education requires English teachers to design learning that is meaningful, student-centered, technology-supported, and relevant to students’ future workplace communication needs. However, limited attention has been given to how vocational English teachers make sense of deep learning pedagogy and translate it into classroom practice after professional development. This qualitative case study examined five experienced vocational English teachers in a vocational school in Yogyakarta that had undergone curriculum reform and required teachers to incorporate deep learning-oriented pedagogy. Data were collected through semi-structured interviews and classroom observation notes and analyzed using reflexive thematic analysis. The findings show that teachers interpreted deep learning as pedagogical renewal within existing curriculum demands. Their adaptation, however, was shaped by school leadership, workload, facilities, mentoring, students’ readiness, and access to professional learning opportunities. Teachers enacted deep learning pragmatically through technology-supported and module-based English teaching, including digital tools, project-based tasks, multimodal activities, and contextualized learning materials. The study contributes to vocational English education research by showing that deep learning pedagogy is enacted through teacher sense-making, institutional negotiation, and classroom-level adaptation rather than as a fixed instructional model.